Distinct transduction of muscle tissue in mice after systemic delivery of AAVpo1 vectors - Tulalamba, Warut; Weinmann, Jonas; El Andari, Jihad; Grimm, Dirk (Gene therapy, 2020)
The human musculature is a promising and pivotal target for human gene therapy, owing to numerous diseases that affect this tissue and that are often monogenic, making them amenable to treatment and potentially cure on the genetic level. Particularly attractive would be the possibility to deliver clinically relevant DNA to muscle tissue from a minimally invasive, intravenous vector delivery. To date, this aim has been approximated by the use of Adeno-associated viruses (AAV) of different serotypes (rh.74, 8, 9) that are effective, but unfortunately not specific to the muscle and hence not ideal for use in patients. Here, we have thus studied the muscle tropism and activity of another AAV serotype, AAVpo1, that was previously isolated from pigs and found to efficiently transduce muscle following direct intramuscular injection in mice. The new data reported here substantiate the usefulness of AAVpo1 for muscle gene therapies by showing, for the first time, its ability to robustly transduce all major muscle tissues, including heart and diaphragm, from peripheral infusion. Importantly, in stark contrast to AAV9 that forms the basis for ongoing clinical gene therapy trials in the muscle, AAVpo1 is nearly completely detargeted from the liver, making it a very attractive and potentially safer option.
Gesehen am 17.04.2020
Published online: 17 October 2019